Seroepidemiology of hepatitis B virus infection among Chinese schizophrenia patients - Huijuan Zhu; Xingxiang Liu; Yong Xue; Chong Shen; Yinghui Li; Aili Wang; Yi Ding; Zhi Zheng; Chen Dong (Journal of Infection in Developing Countries)
Introduction: This study aimed to analyze the characteristics of HBsAg, HBsAb, coexistence of HBsAg and HBsAb, and the genotypic distribution of HBV in Chinese schizophrenia patients. Methodology: A total of 1,694 schizophrenia patients, 9-85 years of age, were recruited for the present study. HBsAg, HBsAb, and HBV DNA were detected with commercial methods. ALT, AST, γ-GT, TBIL, and IBIL were measured by an automatic biochemistry analyzer. All statistical analyses were performed with SPSS 13.0. Results: The seroprevalence of HBsAg and HBsAb in 1,649 schizophrenia patients was 11.0% and 54.6%, respectively. HBsAb seroprevalence significantly decreased with the duration of the disease (p = 0.0009). The lowest seroprevalence of HBsAg was determined in 9.4% of the patients who had had the illness for < 1 year, and then increased to 11.7%, 11.3% and 11.7% in the patients who had had the illness for 1–5 years, 6–10 years and > 10 years. HBsAg and HBsAb coexisted in 69 individuals, which comprised 4.2% of the total subjects, and in 38.1% of the HBsAg-positive patients. Additionally, HBV titers were quantified in 64 HBsAg-positive samples; the highest virus titer was 6.14×108 copies/mL, while 12 patients had less than 500 copies/mL. Moreover, among 48 HBV strains isolated from 62 HBsAg-positive samples, 33 and 15 strains belonged to genotypes C and B, respectively. Conclusion: Genotypes B and C HBV were the dominant genotypes distributed in schizophrenia patients, and the HBsAb seroprevalence significantly decreased with illness duration. Effective prevention strategies for against HBV transmission are required.